Inter-group dynamics within AD Hoc coalitions in the Province of Iloilo. - Casador, Angeli Ness P.; Guillen, Angelo Karlo T. (2008.)
The paper is a study on the dynamics within two ad hoc coalitions in Iloilo City, namely Hugpong Transport and Save Our Lives, SOS!. These coalitions emerged in response to the Iloilo City Perimeter Boundary Ordinance (PBO) and the Guimaras spill, respectively. the most striking features of ad hoc coalitions are contained in the processes of decision-making, which follows the principle of consensus-building, and coalition formation and maintenance, which involves continues alliance work. In all aspects of coalition-building, member-groups were classified as either core groups or periphery groups depending on their level of participation. Apart from differences in the membership base, sectoral and multi-sectoral coalitions operate according to similar processes and principles and encounter mor or less the same problem.
Research Project (Undergraduate, Bachelor of Arts in Political Science) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo.
Keywords: Hugpong Dynamics -- Iloilo, Province of; Save Our Lives, SOS! -- Group Dynamics